Continuance Intention to Use Online Travel Agent Applications in Post-Pandemic in Indonesia: Technology Acceptance Model Theory - Lianna, Wijaya; Dwi, Susanto; Indah Apri, Kusumahati; Putri Arum, Prameswari (INTI International University, 2023)
This study aims to investigate the factors that influence travelers' intentions to continue using Online Travel Agents (OTA) applications in the post-pandemic era, using the technology acceptance model as a framework. This study used the quantitative method to evaluate the data obtained. In total, 240 users of the Online Travel Agents application in Indonesia have been analyzed with Structural Equation Modeling Smart Partial Least Square 3.2.9 for measurement and structural model analysis. The results found that perceived ease of use and perceived usefulness have an influence on trust in using OTA applications and trust influences the continuance intention in using OTA applications in post-pandemic. Understanding the evolution of online travel agent applications in the era following the pandemic is crucial for policymakers and stakeholders in the tourism industry. This understanding can assist in making well-informed decisions regarding regulations, infrastructure, and resource allocation, which are essential for supporting the growth and development of these platforms in the post-pandemic travel landscape. Additionally, examining the utilization of online travel agent applications in the context of the post-pandemic era can provide insights into the role of technology in shaping and influencing travel behavior and decision-making. Furthermore, it can also contribute to the identification of effective strategies for attracting tourists and promoting sustainable tourism practices through regulations, investments, and marketing efforts.